2014
DOI: 10.1136/postgradmedj-2011-201275rep
|View full text |Cite
|
Sign up to set email alerts
|

Republished: Pro-arrhythmic and pro-ischaemic effects of inhaled anticholinergic medications

Abstract: The majority of deaths in COPD are from cardiovascular causes. Several large randomized controlled trials demonstrate that inhaled anticholinergic agents ipratropium and tiotropium increase the risk of serious cardiovascular events, including cardiovascular mortality. Tiotropium Respimat is associated with a statistically significant increased risk of mortality (RR 1.52; 95% CI 1.06 to 2.16) and cardiovascular death (RR 2.05; 95% CI 1.06 to 3.99) compared with placebo in a meta-analysis of clinical trials. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…Salpeter et al, 19 in a meta-analysis of 33 placebo-controlled RCTs, demonstrated an increased risk of cardiovascular events with SABA and LABA in patients with COPD and asthma. Singh et al, 20,28 in a meta-analysis of 17 RCTs, showed an increased risk of a composite end point of cardiovascular death, myocardial infarction or stroke for ipratropium and tiotropium compared to placebo. However, reanalysis of Singh et al 29 in 2008 when UPLIFT trial data was added failed to show an increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Salpeter et al, 19 in a meta-analysis of 33 placebo-controlled RCTs, demonstrated an increased risk of cardiovascular events with SABA and LABA in patients with COPD and asthma. Singh et al, 20,28 in a meta-analysis of 17 RCTs, showed an increased risk of a composite end point of cardiovascular death, myocardial infarction or stroke for ipratropium and tiotropium compared to placebo. However, reanalysis of Singh et al 29 in 2008 when UPLIFT trial data was added failed to show an increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of COPD in patients with concomitant AF should be the same as those without AF. Bronchodilators have been described as potential proarrhythmic agents (200,201), but available evidence suggests an overall acceptable safety profile for using LABA, LAMA, and ICS (202,203). For example, tiotropium does not increase the overall risk of cardiac arrhythmias (204), whereas a slightly higher incidence of AF has been reported in patients treated with glycopyrronium compared with placebo, despite an overall good safety profile (104).…”
Section: Treatment Of Copd In Patients Withmentioning
confidence: 99%
“…26,27 However, they increase the risk of cardiovascular morbidity and mortality. 28,29 They require cautious use in patients having cardiac disorders. Amlodipine is well tolerated and effective antihypertensive.…”
Section: Discussionmentioning
confidence: 99%